The Provincial Officer of the Central Army: Kethüdâyeri and Its Role in the Ottoman Military Organization - Coşkun Ünsal (Tarih Dergisi)
Until the mid-16th century, the Kapıkulu cavalry, as a core component of the regular Ottoman army, resided primarily in the capital or nearby areas. However, in the latter half of the century, they began to establish a presence in various parts of the empire. Their desire to maintain military privileges even in distant administrative units and their tendency to reject interference from anyone other than their own commanders, led to significant challenges in the Ottoman provinces. To maintain discipline among the Kapıkulu cavalry, who had begun residing in the provinces and gradually integrating into the local population, and to ensure effective mobilization while the Ottoman state initiated the appointment of officers after the 1570s. The appointments of these officials known as Kethüdâyeri became systematic from the early 17th century onwards. Existing information on the kethüdâyeris, who were to become one of the most important actors in the provincial administration, is quite limited. Therefore, it is necessary to prepare a ground for analytical studies. The main purpose of this study is to examine various aspects of the kethudâyeris in a descriptive manner. In the introductory part of the study, the developments that led to the emergence of the kethudāyeris within the context of military transformation will be analyzed. Then, the appointment procedure, who were selected and what qualifications they possessed will be explained with examples. The study argues that the appointment of kethüdâyeri emerged in response to legal, military, and social needs, and over time, these officers became instrumental in maintaining public order in the provinces. Also, it will contend that they were influential figures within their regions prior to their appointment or gained such influence following their appointment. All these explanations will be made by pointing out the transformations and exceptions in the process as much as possible. The primary sources for this research are Ottoman archival records and other contemporary documents.